Identification of Novel Hub Genes Associated with Inflammation and Autophagy in Astragaloside Membranaceus ameliorates Lupus Nephritis by Bioinformatics Analysis and Molecular Dynamics Simulation - Kong, Kaili; Qiao, Xiaomei; Liu, Ting; Wang, Xiaoxia; Li, Rui; Fang, Jingai; Zhang, Xiaodong (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundLupus nephritis is an autoimmune disease, and its pathogenesis involves inflammation and autophagy disorders. Studies have demonstrated that Astragalus membranaceus can effectively suppress the progression of LN, but the underlying therapeutic target is still unclear.ObjectionThis study aimed to investigate the therapeutic target whereby AM ameliorates LN.MethodsWe downloaded AM and LN-related chips from the TCMSP and GEO databases, respectively. We selected the two compound targets for the subsequent analysis via WGCNA, and constructed protein interaction networks of compound targets and determined the core targets. GO, KEGG analyses were conducted on compound targets to identify enriched functional and genomic pathways. The core genes were further validated in clinical and external datasets. Molecular docking of AS with the core targets was performed using the AutoDock software, and molecular dynamics simulation was conducted for the optimal core protein ligand obtained by molecular docking by Gromacs 2020.6 software.ResultsWe obtained 10 core targets, namely IL-1β, EGF, CCND1, CASP3, STAT1, PTGS2, PPARγ, AR, CXCL10, and KDR, from the 24 compound targets identified. The results of the GO enrichment analysis mainly included cell growth regulation. The results of the KEGG enrichment analysis showed that 7 out of 23 valid targets were significantly enriched in the mitogen-activated protein kinase pathway (p < 0.01). Combined with the clinical datasets, we found that IL-1β, EGF, CCND1, CASP3, STAT1, PTGS2, and PPARγ have high diagnostic values for LN. In the validation dataset, all the core targets were significantly differentially expressed, except for EGF deletion. The molecular docking and molecular dynamics simulation results showed that AM and IL-1β, CASP3, STAT1, and PPARγ all had binding energies < -5 kJ·mol-1 and good binding properties.ConclusionIL-1β, CASP3, STAT1, and PPARγ could be potential biomarkers and therapeutic targets in AM ameliorates LN.
Keywords: inflammation